The Validity of the Exoneration Clause in Ship Repair Contracts: Legal Protection for Shipyard Service Users - Muhammad Ridwan; Sri Astutik; M Syahrul Borman (LUTUR Law Journal, 2026)
The practice of ship repair contracts in shipyards often contains exoneration clauses that limit or even remove the service provider's liability for certain damages. This condition has the potential to cause an imbalance in the legal position between the shipyard and the service user, especially when the clause is drafted unilaterally. This study aims to analyze the validity of the exoneration clause in the ship repair contract and assess the extent to which the clause provides legal protection for shipyard service users reviewed from the principle of balance and freedom of contract. The research method used is normative legal research with a statutory and conceptual approach, through the study of the provisions of the Civil Code, regulations related to shipping services, and contract law doctrine. The results of the study show that the exoneration clause is allowed in principle as long as it does not conflict with law, decency, and public order. However, clauses that eliminate absolute liability tend to violate the principle of balance and have the potential to harm service users. Therefore, it is necessary to formulate proportional clauses so that ship repair contracts continue to provide fair legal protection for the parties.